Using ChatGPT as Artificial Intelligence (Ai) Tool to Improve Students’ English Proficiency - Yoni Rahayu; Muhammad Muslim Nasution; Soraya Grabiella Dinamika; Iis Aprianti (Universitas Islam Negeri Palopo, 2025)
This study examines the role of Artificial Intelligence (AI), particularly ChatGPT, in enhancing English proficiency among Generation Z learners. Using a library-based literature review of academic sources published between 2018–2024 and supported by preliminary observations of 28 students, this research functions as a synthesis of existing studies and does not generate new empirical data. Findings indicate that ChatGPT provides more comprehensive real-time corrective feedback than traditional mobile learning tools and standard grammar checkers, offering explanations, revision options, and personalized input. Prior research reports improvements in writing accuracy, vocabulary development, and learner autonomy when AI tools are integrated into language learning. Generation Z learners also demonstrate strong motivation and engagement when using AI-supported platforms. Overall, the study highlights AI’s potential to accelerate English proficiency and recommends that educators incorporate AI-driven tools to enhance instructional effectiveness and support independent learning.